A study of the composition of the work “Khubilai Khan hunting” - Sergelenbayar, Tsolmontsetseg (Mongolian Journal of Arts and Culture, 2024)
In the royal palace museum of Taiwan Gugun, there is a classic work of the 13th century called “Khubilai Khan hunting”. Since the 20th century, the palace has been exhibited in museums and enjoyed by many domestic enthusiasts. The pleasure that a person gets from any work of art is due to the recognition of the aesthetics, skill and talent of great artists. In addition to a clear explanation of the low of distance in naturae painting in the “three types of distance laws of the surrounding environment”, the ancient X-th century Southern Song art history book on the low of composition in painting, the date of creation of the palace works of the Yuan Dynasty in the 14th century and the color of Mongolian painting There is a historical document called “chronicle of the great ceremony of the dynasty” which has been carefully written from many aspects, such as colors and methods. In has been determined that several compositional techniques of nomadic painting were used in the work “Khubilai Khan hunting” of the Mongolian nomads of the 13th century. Define: 1. In the work, in was performed with the method of “Z- shaped linear design” 2. In the work, the artist has artificially depicted the main and secondary characters with the method of imaginary distance 3. The spatial expression of the creation was made by the combination of virtual and reality 4. The picture is equalized by the aesthetic principle of combining static and dynamic elements 5. The artist arranged ten main and secondary characters in a concentric circle around the center according to nomadic symbolism and rituals 6. Using the “law of connection of image and point of view” of portrait painting, he made the partial figures of the picture into a unified whole 7. The position of the main and secondary characters of the work is designed by the method of “imagining yourself as the main character” 8. In his work, the artist has used a variety of distance laws and compositional methods, such as imaginary distance, color distance, and image distance in a proper coordination. “Хубилай хаан авд мордсон нь” бүтээлийн зохиомжийн судалгаа Хураангуй: Тайваны Гугун хааны ордон музейд ХIII зууны аж байдлын сэдэвт “Хубилай хаан авд мордсон нь” хэмээх сонгодог уран бүтээл хадгалагдаж буй. XX зуунаас хойш ордон музей чөлөөтэй дэлгэгдсэнээс гадаад дотоодын олон арвин сонирхогчдын таашаалыг хүртсээр иржээ. Ямарваа нэгэн уран бүтээлээс тухайн хүний олж байгаа таашаал нь зураачдын гоо зүй, ур чадвар, авьяас билиг хүлээн зөвшөөрөгдсөнийх биз ээ. Уран зургийн зохиомжийн хуулийн тухай эртний Х зууны Өмнөд Сүн улсын урлагийн түүхэн бичиг “Задгай орчны гурван төрлийн алслалтын хууль”-д байгалийн уран зургийн алслалтын хуулийг нарийн тодорхой тайлбарласнаас гадна ХIV зууны Юань гүрний ордны бүтээлүүдийн бүтээгдсэн он цаг, монгол уран зургийн өнгө будаг, арга барил зэрэг олон талаас нягтлан бичсэн “Хаан гүрний их ёслолын шастир” хэмээх түүхэн сурвалж бичиг бий. XIII зууны монгол угсааны нүүдэлчдийн уран зураг “Хубилай хаан авд мордсон нь” бүтээлд нүүдэлчдийн уран зургийн уламжлалт хэд хэдэн зохиомжийн арга барилыг хавсарган хэрэглэснийг тодорхойллоо. Үүнд: 1. Бүтээлийг “Z хэлбэрт чиглүүлэгч шугаман зохиомж”-ийн арга барилаар гүйцэтгэсэн. 2. Бүтээлд зураач гол, дэд дүрээ төсөөллийн алслалтын арга барилаар зохиомжлон дүрсэлсэн. 3. Виртуал ба бодит байдлын хослол арга барилаар бүтээлийн орон зайн илэрхийлэл хийгдсэн. 4. Статик ба динамик байдлыг харилцан хувирган нэгтгэх гоо зүйн зарчмаар зургийг тэнцвэржүүлсэн. 5. Зураач гол, дэд дүр болох нийт арван хүмүүнээ төвөө даган төвлөрсөн тойрог хэлбэртэй зохиомжлохдоо нүүдэлчдийн бэлгэдэл зүй, тайлга тахилгын зан үйлийн дагуу байрлуулжээ. 6. Хөрөг зургийн “дүрс ба харааны цэгийн холбоосны хууль”-ийг ашиглан зургийн хэсэгчилсэн дүрүүдээ нэгдмэл цогц болгосон. 7. Бүтээлийн гол, дэд дүрүүдийн байрлалаа “өөрийгөө гол дүр болгон төсөөлөн дүрслэх” арга барилаар зохиомжилсон. 8. Зураач бүтээлдээ төсөөллийн алслалт, өнгөний алслалт, дүрсийн алслалт зэрэг олон төрлийн алслалтын хууль, зохиомжийн арга барилуудыг зохистой уялдуулан ашиглажээ. Түлхүүр үгс: монгол уран зураг, ур ухаан, арга барил, зохиомж, урлаг, дүр дүрслэл, алслалт, орон зай